1995
DOI: 10.1016/s1059-1311(95)80090-5
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile myoclonic epilepsy and human leukocyte antigens

Abstract: The idiopathic generalized epilepsies (IGE) occur with a high aggregation within families. Juvenile myoclonic epilepsy (JME) is recognized as a commonly occurring form of idiopathic generalized epilepsy. A possible association between JME and HLA antigens was investigated by serological typing of human leukocyte antigens (HLA) class I antigens and by DNA oligotyping of class II antigens. Twenty-four patients and 129 controls, all Caucasians of Scandinavian descent, were tested. Uncorrected there was a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In relation to representativeness of the controls, fifty-six percent were either population–based or healthy volunteers[36,3842,45,46,48,5153,55,58,6265,67,6972,74,77,80,82,83] and forty-five percent were both population-based and hospital-based/healthy volunteers/blood donors[34,35,37,43,44,47,49,50,54,56,57,5961,66,68,73,75,76,78,79,81]. Sixty four percent of control matched only one variable (age, gender or ethnicity) with cases[3640,4248,5054,56,57,62,66,68,69,71,73,7579,81,82]. Ninety-two percent clearly described diagnosis for JME[3553,5578,80,82,83].…”
Section: Resultsmentioning
confidence: 99%
“…In relation to representativeness of the controls, fifty-six percent were either population–based or healthy volunteers[36,3842,45,46,48,5153,55,58,6265,67,6972,74,77,80,82,83] and forty-five percent were both population-based and hospital-based/healthy volunteers/blood donors[34,35,37,43,44,47,49,50,54,56,57,5961,66,68,73,75,76,78,79,81]. Sixty four percent of control matched only one variable (age, gender or ethnicity) with cases[3640,4248,5054,56,57,62,66,68,69,71,73,7579,81,82]. Ninety-two percent clearly described diagnosis for JME[3553,5578,80,82,83].…”
Section: Resultsmentioning
confidence: 99%
“…Juvenile myoclonic epilepsy (JME) was shown to be linked to the BF and HLA loci on human chromosome 6 in two population groups from the United States and Germany (45,46) and with HLA-DRW13 (W6) in Arab patients (47). A study from Norway concluded that there was no clue as to a primary HLA-DQ association with JME (48). The report of linkage of convulsions and the EEG trait to the chromosome 6 locus in one large family with JME supports the contention that some "genes" predisposing to the susceptibility to seizures may be located near the HLA locus (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, both Elmslie et al (1996) and failed to find any evidence suggesting linkage of JME to markers centromeric to HLA. Finally, Durner et al (1992), Obeid et al (1994), Greenberg et al (1995), and Moen et al (1995) found evidence of association of JME and HLA alleles.…”
Section: Introductionmentioning
confidence: 87%